2011
DOI: 10.3354/meps09212
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of flows generated by the hydromedusa Aequorea victoria: a Lagrangian coherent structure analysis

Abstract: Most oblate medusae use flow generated during swimming to capture prey. Quantification of their interactions with surrounding fluid is necessary to understand their feeding mechanics and to develop models to predict their predatory impact. In the present study, we quantified how the hydromedusa Aequorea victoria interacts with both its surrounding fluid and prey. The fluid interactions were examined in the laboratory and in natural field settings using digital particle image velocimetry (DPIV) measurements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
(83 reference statements)
3
24
0
1
Order By: Relevance
“…kinetic energy and impulse) using planar measurement data (Katija and Dabiri, 2009;Katija et al, 2011). An in-house Matlab code was used to compute the time-varying specific fluid kinetic energy KE(t)/ρ and specific fluid impulse I(t)/ρ in the wake generated by swimming S. tubulosa.…”
Section: −3mentioning
confidence: 99%
“…kinetic energy and impulse) using planar measurement data (Katija and Dabiri, 2009;Katija et al, 2011). An in-house Matlab code was used to compute the time-varying specific fluid kinetic energy KE(t)/ρ and specific fluid impulse I(t)/ρ in the wake generated by swimming S. tubulosa.…”
Section: −3mentioning
confidence: 99%
“…This is advantageous in drawing prey onto capture surfaces located in this region of maximum flow throughout the entire duration of the pulse (Larson, 1991;Dabiri et al, 2005). Few studies have quantified the fluid dynamics associated with prey capture by these rowing medusae (Katija et al, 2011); however, it has been shown that the generation of a feeding current by rowing medusae is energetically efficient and effective at circulating large volumes through trailing capture surfaces (Dabiri et al, 2005). These traits enable rowing medusae to forage continuously as feeding-current feeders (Colin and Costello, 2002;Colin et al, 2003;Kiørboe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Esse colágeno da mesogléia umbrelar, na forma de feixes, armazena a energia potencial elástica gerada pela contração e age em ação antagônica à musculatura subumbrelar, para a recuperação da forma inicial da umbrela (Muskatine & Lenhoff, 1974;. Tal propriedade mecânica da umbrela de medusas Rhizostomeae propicia maiores volumes de água transportados contra os braços orais, e assim aumenta o volume filtrado (Acuña et al, 2011;Katija et al 2011).…”
Section: Rhizostomeaeunclassified
“…and Pelagia noctiluca) (Addad et al 2011). The remarkable hardiness of rhizostome medusae bell allows higher swimming, and potentially feeding performance, since the volume of cleared water depends on the volume of entrained water by bell contractions (Acuña et al 2011;Katija et al 2011). Whereas some semaeostome medusae enhance prey encounter rates by developing long capture structures, such as in C. capillata which bears tentacles up to 10 m long , rhizostomeae medusae have high frequency swimming patterns which allow lager volume of fluids filtered and also higher encounter rates with prey.…”
Section: Swimming Kinematics Among Scyphomedusaementioning
confidence: 99%
See 1 more Smart Citation